Photoelectric and Thermoelectric Dual Modulation Via a Ternary Composite. Issue 5 (18th December 2018) - Sun, Sam‐Shajing; Lee, Harold Odell
Abstract: Materials for simultaneous photoelectric and thermo‐electric dual conversions and modulations, where photon can modulate the thermoelectric conversion, and temperature can modulate the photoelectric conversion, may find potential applications where light (including a laser) can remotely turn on, turn off, or modulate a thermoelectric generator, a cooler, or a temperature sensor, and vice versa, temperature (heating/cooling) can turn on, turn off, or modulate a photoelectric device such as a photo detector or a solar cell. Here, it is demonstrated that such simultaneous dual conversion or modulation can be achieved via a ternary composite, e.g., a poly‐3‐hexyl‐thiophene thin‐film doped with both phenyl‐C61‐butyric acid methyl ester and iodine. This finding may result in the development of lightweight, flexible shape, cost‐effective, renewable, environmentally friendly, biocompatible, and scalable materials, devices, and systems for clean energy harvestings (such as solar and waste heat dual energy harvesting) as well as light/heat dual‐sensing sensors, modulators, and controllers. Abstract : Materials for simultaneous photoelectric and thermoelectric dual conversions may find potential applications where light can remotely modulate a thermoelectric generator, and vice versa, temperature can modulate a photoelectric device simultaneously. It is demonstrated that such simultaneous dual conversion or modulation material can be achieved via a ternary composite.